The effect of primary school entrepreneurship education programs on the evolution of pupils' human capital assets - Gorenc, Janez (Economic and business review, 2023)
The formation of entrepreneurship-related human capital in primary-school entrepreneurship education programs (EEPs) is of great interest to European policymakers. European education systems have widely implemented EEPs since the Oslo Agenda for entrepreneurship education in Europe was passed in 2006. However, primary-school EEPs remain an underresearched domain of entrepreneurship education. The present article investigates the development of entrepreneurship-related human capital in EEPs for 9-14-year-olds in 22 primary schools. It uses a quasi-experimental design with repeated measures. Based on data obtained from a sample of 180 participants, the analysis finds that the whole group partly improved only one of the components of human capital. However, the given EEPs positively impact the development of certain components of entrepreneurship-related human capital when investigated through the lens of entrepreneurial family background or gender. When subset by gender, results show that girls improved some components, while boys upgraded others. Also, pupils from entrepreneurial families improved more of the measured constructs than pupils from non-entrepreneurial families. The study provides valuable insights into the evolution of human capital among early adolescents in primary-school EEPs and uses human capital theory to explain this development. It also supplies evidence of the positive effect of EEPs on individuals of specific social groupings. Theoretical and practical implications are discussed and guidelines for further research are provided.
Keywords: elementary school; entrepreneurship; izobraževanje; learning; osnovno šolstvo; podjetništvo